Satirical argument in political discourse - rym, Cherif (Arab Journal for Sciences and Research Publishing, 2020)
The aim of this research is to identify the concept of arguments as an interactive linguistic phenomenon produced by society following a communication and intellectual revolution and the increased use of the concept of arguments more after the outbreak of the so- called "spring revolution" at all levels without exception in order to persuade and influence and reveal the hidden to the public. In particular, the political arguments originally depended on systematic and studied persuasion. But, after the revolution, there became picture arguments dependent on the mockery in which the image is used to express the idea to be communicated, which gives a new persuasive character. Thus, the research reached the following results:- That sarcasm has multiple and varied dimensions revealed by political and social articles.- The study also revealed that the arguments of satire is a creative art in which the whole complex represented in language, thought, art and philosophy is mixed.- Irony is a position on life issues, an expression of the idea and a challenge to a specific situation, especially the status of a specific issue that has a political dimension.- The results also showed that satirical images are a weapon of much resistance to corruption, as they are considered a manifestation of popular resistance and rebellion against injustice, by depicting them in a comic manner.
Keywords: Hajjaj; Satire; Political satire; Image